2013
DOI: 10.3791/50172
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Respiratory System Mechanics in Mice using the Forced Oscillation Technique

Abstract: The forced oscillation technique (FOT) is a powerful, integrative and translational tool permitting the experimental assessment of lung function in mice in a comprehensive, detailed, precise and reproducible manner. It provides measurements of respiratory system mechanics through the analysis of pressure and volume signals acquired in reaction to predefined, small amplitude, oscillatory airflow waveforms, which are typically applied at the subject's airway opening. The present protocol details the steps requir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
112
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 102 publications
(115 citation statements)
references
References 27 publications
2
112
0
1
Order By: Relevance
“…Thus, although proinflammatory processes are elevated by C5a after LPS exposure in C5L2 2/2 mice, these processes, in turn, result in elevated production of suppressive processes. To determine whether the changes in inflammatory parameters observed after LPS administration to C5L2 2/2 and wildtype mice correlated with changes in lung physiology, we examined a number of mechanical parameters of the animals using a technique of forced oscillation to determine pressure and volume signals (31). Consistent with literature reports indicating little or no alteration in lung physiology despite increased inflammatory cell infiltrates and cytokine production (32, 33), our findings indicated that wild-type mice at 48 hours after LPS administration exhibited no significant change in total lung volume, resistance, or elastic recoil, although dynamic compliance was reduced ( Figures 6A-6D).…”
Section: C5l2mentioning
confidence: 99%
“…Thus, although proinflammatory processes are elevated by C5a after LPS exposure in C5L2 2/2 mice, these processes, in turn, result in elevated production of suppressive processes. To determine whether the changes in inflammatory parameters observed after LPS administration to C5L2 2/2 and wildtype mice correlated with changes in lung physiology, we examined a number of mechanical parameters of the animals using a technique of forced oscillation to determine pressure and volume signals (31). Consistent with literature reports indicating little or no alteration in lung physiology despite increased inflammatory cell infiltrates and cytokine production (32, 33), our findings indicated that wild-type mice at 48 hours after LPS administration exhibited no significant change in total lung volume, resistance, or elastic recoil, although dynamic compliance was reduced ( Figures 6A-6D).…”
Section: C5l2mentioning
confidence: 99%
“…The mechanical properties of the respiratory system were assessed using single frequency (2.5 Hz; Snapshot-150, 1.2 s) and broadband forced oscillation signals (1-20.5 Hz; Quick Prime-3, 3 s) as well as a quasi-static, step-wise, pressure-controlled pressure-volume loop (PVs-P, 16 s) (McGovern et al, 2013). The linear single-compartment model was used to evaluate total respiratory resistance (R rs ) and elastance (E rs ) while the constant phase model allowed the partitioning of the responses within the lungs (Hantos et al, 1992).…”
Section: Methodsmentioning
confidence: 99%
“…This protocol uses a small animal ventilator to measure reductions in the elastic recoil of the lung (increases in quasistatic lung compliance [Cst] and reductions in tissue elastance [H]), PV flow loops, and changes in airway and tissue resistance in anesthetized mice (15,16) .…”
Section: Pulmonary Function Test (Pfts)mentioning
confidence: 99%